The Impact of MAMO Mobile Application-Based Microlearning on Students’s Comprehension in Creating Procedural Text in Junior High School - Zhafharina, Anna (Foremost Journal, 2025)
This research explores about The Impact of MAMO Mobile Application Based Microlearning on Students’s Comprehension in Creating Procedural text in Junior High School. This type of research is experimental research using One group pre-test and post-test. The sample in this study was 35 9th-grade students. The instruments used were pre-test and post-test. So based on the results of the calculation of students' understanding ability in making procedural texts, the Asymp. Sig (2-tailed) value is 0.001 <0.05. In addition, an N-gain score is 0.7607 > 0.76 was found. By considering the Asymp. Sig (2-tailed) value obtained, it can be concluded that there is an influence between the Microlearning learning model through the MAMO mobile application on the understanding ability of 9th-grade students at SMP Benteng Gading. Based on the N-gain value, it can also be concluded that the Microlearning learning model is more effective in improving students' comprehension.